2017
DOI: 10.1038/s41598-017-09087-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of magnetized quark-nuggets, a candidate for dark matter

Abstract: Quark nuggets are theoretical objects composed of approximately equal numbers of up, down, and strange quarks and are also called strangelets and nuclearites. They have been proposed as a candidate for dark matter, which constitutes ~85% of the universe’s mass and which has been a mystery for decades. Previous efforts to detect quark nuggets assumed that the nuclear-density core interacts directly with the surrounding matter so the stopping power is minimal. Tatsumi found that quark nuggets could well exist as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(82 citation statements)
references
References 52 publications
(112 reference statements)
0
82
0
Order By: Relevance
“…In this respect we emphasize that, in addition to radio observations at 21 cm to map the HI component of the gas (integrated also by other techniques to study small-scale cold structures as done, e.g., through interstellar scintillations by Habibi et al 2011) and to the X-ray band diffuse emission to infer the amount and distribution of the hot gas component, investigation of the warm gas component with the methodology employed, e.g., in Nicastro et al (2016) is extremely important. Given the serious quantitative disagreement between the microwave temperature asymmetry amplitude revealed for M81 and several other nearby galaxies and the rkSZ contributions there, the latter's alternative may be more exotic halo models (see, e.g., Lovell et al 2016;Okumura et al 2017;Piras et al 2017;Pace VanDevender et al 2017;Gurzadyan and Kocharyan 2009), a dilemma to be solved by future studies.…”
mentioning
confidence: 99%
“…In this respect we emphasize that, in addition to radio observations at 21 cm to map the HI component of the gas (integrated also by other techniques to study small-scale cold structures as done, e.g., through interstellar scintillations by Habibi et al 2011) and to the X-ray band diffuse emission to infer the amount and distribution of the hot gas component, investigation of the warm gas component with the methodology employed, e.g., in Nicastro et al (2016) is extremely important. Given the serious quantitative disagreement between the microwave temperature asymmetry amplitude revealed for M81 and several other nearby galaxies and the rkSZ contributions there, the latter's alternative may be more exotic halo models (see, e.g., Lovell et al 2016;Okumura et al 2017;Piras et al 2017;Pace VanDevender et al 2017;Gurzadyan and Kocharyan 2009), a dilemma to be solved by future studies.…”
mentioning
confidence: 99%
“…In contrast, conducting plasma shorts out the electric field and prevents particle penetration. A MQN moving through a plasma experiences a greatly-enhanced slowing down force 16 through its magnetopause, which is the magnetic structure formed by particle pressure from a plasma stream balancing magnetic field pressure around a magnetic dipole. For example, the solar wind forms a magnetopause with Earth's magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…1. self-magnetic field aggregates MQNs with baryon number A = 1 into MQNs with a broad mass distribution 4 that is characterized by the value of B o and typically has A between ~ 10 3 and 10 37 , 2. aggregation dominates decay by weak interaction so massive MQNs can form and remain magnetically stabilized in the early universe even though they have not been observed in particle accelerators 4 , 3. the self-magnetic field forms a magnetopause that strongly enhances the interaction cross section of a MQN with a surrounding plasma 16 that is primarily sustained by radiation and electron impact ionization in the high temperature plasma formed by normal matter stagnating against the magnetopause, 4. B o > 3 × 10 12 T is excluded 4 by the lack of observed deeply penetrating impacts that deposit > Megaton-TNT equivalent energy per km, so Tatsumi's range of B S is reduced to 1 × 10 11 T ≤ B o ≤ 3 × 10 12 T, 5.…”
mentioning
confidence: 99%
“…Various experiments have tried to produce or search for SQM in various environments, on the ground, on balloons and in satellites, both of active and passive nature. A review on strangelet search and models can be found in [26,27]. SQM should be neutral (uncharged), if an exactly equal number of u, d, and s quarks is dynamically favoured, however the neutrality condition may be approximate, allowing strangelets to have a small residual electrical charge.…”
Section: Strange Quark Matter and Strangeletsmentioning
confidence: 99%